Overall Survival With Daratumumab, Lenalidomide, and Dexamethasone in Previously Treated Multiple Myeloma (POLLUX): A Randomized, Open-Label, Phase III Trial. Issue 8 (4th January 2023) - Dimopoulos, Meletios A.; Oriol, Albert; Nahi, Hareth; San-Miguel, Jesus; Bahlis, Nizar J.; Usmani, Saad Z.; Rabin, Neil; Orlowski, Robert Z.; Suzuki, Kenshi; Plesner, Torben; Yoon, Sung-Soo; Ben Yehuda, Dina; et al.
Abstract : PURPOSE: With the initial analysis of POLLUX at a median follow-up of 13.5 months, daratumumab in combination with lenalidomide and dexamethasone (D-Rd) significantly prolonged progression-free survival versus lenalidomide and dexamethasone (Rd) alone in patients with relapsed or refractory multiple myeloma (RRMM). We report updated efficacy and safety results at the time of final analysis for overall survival (OS). METHODS: POLLUX was a multicenter, randomized, open-label, phase III study during which eligible patients with ≥ 1 line of prior therapy were randomly assigned 1:1 to D-Rd or Rd until disease progression or unacceptable toxicity. After positive primary analysis and protocol amendment, patients receiving Rd were offered daratumumab monotherapy after disease progression. RESULTS: Significant OS benefit was observed with D-Rd (hazard ratio, 0.73; 95% CI, 0.58 to 0.91; P = .0044) at a median (range) follow-up of 79.7 months (0.0-86.5). The median OS was 67.6 months for D-Rd compared with 51.8 months for Rd. Prespecified analyses demonstrated an improved OS with D-Rd versus Rd in most subgroups, including patients age ≥ 65 years and patients with one, two, or three prior lines of therapy, International Staging System stage III disease, high-risk cytogenetic abnormalities, and refractoriness to their last prior line of therapy or a proteasome inhibitor. The most common (≥ 10%) grade 3/4 treatment-emergent adverse events with D-Rd versus Rd were neutropenia (57.6% v 41.6%), anemia (19.8% v 22.4%), pneumonia (17.3% v 11.0%), thrombocytopenia (15.5% v 15.7%), and diarrhea (10.2% v 3.9%). CONCLUSION: D-Rd significantly extended OS versus Rd alone in patients with RRMM. To our knowledge, for the first time, our findings, together with the OS benefit observed with daratumumab plus bortezomib and dexamethasone in the phase III CASTOR trial, demonstrate OS improvement with daratumumab-containing regimens in RRMM (ClinicalTrials.gov identifier: NCT02076009 [POLLUX]).